The Unique Brain Anatomy of Meditation Practitioners: Alterations in Cortical Gyrification - Luders, Eileen; Kurth, Florian; Mayer, Emeran A.; Toga, Arthur W.; Narr, Katherine L.; Gaser, Christian (Frontiers in Human Neuroscience, 2012)
Several cortical regions are reported to vary in meditation practitioners. However, since prior analyses were focused on examining gray matter or cortical thickness, additional effects with respect to other cortical features might have remained undetected. Gyrification (the pattern and degree of cortical folding) is an important cerebral characteristic related to the geometry of the brain’s surface. Cortical folding occurs early in development and might be linked to behavioral traits. Thus, exploring cortical gyrification in long-term meditators may provide additional clues with respect to the underlying anatomical correlates of meditation. This study examined cortical gyrification in a large sample (n=100) of meditators and controls, carefully matched for sex and age. Cortical gyrification was established via calculating mean curvature across thousands of vertices on individual cortical surface models. Pronounced group differences indicating larger gyrification in meditators were evident within the left precentral gyrus, right fusiform gyrus, right cuneus, as well as left and right anterior dorsal insula (the latter representing the global significance maximum). Although the exact functional implications of larger cortical gyrification remain to be established, these findings suggest the insula to be a key structure involved in aspects of meditation. For example, variations in insular complexity could affect the regulation of well-known distractions in the process of meditation, such as daydreaming, mind-wandering, and projections into past or future. Moreover, given that meditators are masters in introspection, awareness, and emotional control, increased insular gyrification may reflect an ideal integration of autonomic, affective, and cognitive processes. Due to the cross-sectional nature of this study, further research is necessary determine the relative contribution of nature and nurture to links between cortical gyrification and meditation.